Effect of Globalisation in Recruitment policies in Nigeria (Global Journal of Management and Business Research, 2018)
The aim of this study is to advance prior knowledge on recruitment by empirically investigating how this phenomenon is affected by globalization in the context of manufacturing firm in South Eastern, Nigeria. It adopts the survey design. The population and the sample size is 271. The sources of data were both primary and secondary. The instruments for data collection are the questionnaire and semistructured interview for the primary data while text books, journals, magazines and the internet were used for the secondary data. The questionnaire was designed along the five point likert scale. A content validity approach was adopted. The test-retest method was used for the reliability test which gave a reliability coefficient of .80 which suggested a high degree of consistency. The data collected were analyzed and the hypotheses were tested using analysis of variance (ANOVA) while the significance test of the F value was determined by the correlation ratio (CE) at P≤.05. The result of the study revealed that manpower planning, policies and preparations associated with recruitment differ significantly with the effects of globalization. Training and professional development do not differ with the effects of globalization; reward and compensation differ significantly with the effects of globalization. The study concluded that hiring good people is the key source of competitive advantage and as such organization must approach recruitment from a rigorous strategic and objective point of view through international best practices.